2011
DOI: 10.1016/j.jbankfin.2011.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Extreme returns: The case of currencies

Abstract: a b s t r a c tFinancial market crashes can occur even in the absence of news. This paper highlights four properties of price-contingent trading that increase the frequency of such events. Price-contingent trading is common across financial market, since it includes algorithmic trading, technical trading, and dynamic option hedging. The four properties we consider are: (1) high kurtosis in the distribution of order sizes; (2) clustering of trades within the day; (3) clustering of trades at certain prices; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Hashimoto et al (2010) show that a "run" 1 has some predictive power on the direction of the next price move. Finally, the mechanisms behind FX rates tail events are studied by Osler and Savaser (2011), who found that price-contingent trading may be a major source of extreme returns.…”
Section: Introductionmentioning
confidence: 99%
“…Hashimoto et al (2010) show that a "run" 1 has some predictive power on the direction of the next price move. Finally, the mechanisms behind FX rates tail events are studied by Osler and Savaser (2011), who found that price-contingent trading may be a major source of extreme returns.…”
Section: Introductionmentioning
confidence: 99%
“…First, as established in e.g. Westerfield (1977), and later Osler and Savaser (2011), the return distribution of foreign exchange rates exhibit excess kurtosis, i.e. possess fat tails compared to the normal distribution.…”
Section: Foreign Exchange Rate Modelingmentioning
confidence: 95%
“…There is however no consensus on the exact form of the distribution, which varies with the timescale. The mechanisms behind FX rates tail events are studied by Osler and Savaser (2011), they have found that pricecontingent trading may be a major source of extreme returns. Figure 1 shows the empirical cumulative distribution of the EUR/USD and USD/JPY positive log-returns.…”
Section: Fat-tailsmentioning
confidence: 99%